2018
DOI: 10.1002/marc.201800546
|View full text |Cite
|
Sign up to set email alerts
|

A Simple, Small‐Bandgap Porphyrin‐Based Conjugated Polymer for Application in Organic Electronics

Abstract: A simple, small-bandgap porphyrin-based conjugated polymer with ethylnyl linkers is prepared for application in organic electronics. Beneficial from quinoid resonance form, the polymer showed near-infrared absorption up to 1000 nm and strong photoluminescence emission with a quantum yield of 0.2%. The polymer can be successfully applied to several electronic devices, such as organic field-effect transistors with ambipolar charge transport, organic solar cells with a high external quantum efficiency of 0.58 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The OPVs fabricated with CS‐DP and PC 71 BM afforded a PCE of 8.29%. Li et al reported a simple porphyrin‐based polymer named PPor1 by using ethylnyl groups as linkers . Due to the quinoid character, the polymer exhibits NIR absorption up to 1000 nm.…”
Section: Nir Photoelectric Materials For Opvsmentioning
confidence: 99%
“…The OPVs fabricated with CS‐DP and PC 71 BM afforded a PCE of 8.29%. Li et al reported a simple porphyrin‐based polymer named PPor1 by using ethylnyl groups as linkers . Due to the quinoid character, the polymer exhibits NIR absorption up to 1000 nm.…”
Section: Nir Photoelectric Materials For Opvsmentioning
confidence: 99%
“…Covalent conjugation occurs through the formation of amide linkages (Fig. 19), 185,186 whereas non-covalent interaction occurs through π-π stacking and effective ionic bonding. 187,188 Fig.…”
Section: Porphyrin-graphene Hybridsmentioning
confidence: 99%
“…19 Covalent and non-covalent nanohybrid formation between a porphyrin and a carbon nanohorn. 185 CNHs are excellent electron acceptors and possess the ability to diffuse the electrons readily along the cone axis with negligible loss of energy. This inspires the formation of electron donoracceptor nanohybrids of CNHs and porphyrins (Fig.…”
Section: Porphyrin-graphene Hybridsmentioning
confidence: 99%
“…This motivated researchers to search for metal-free organic as well as natural dyes for photosensitizers in DSSCs. Recently, many types of research have been carried out in exploring metal-free organic sensitizers both experimentally and theoretically to predict their efficiency as sensitizers in DSSCs [70]. This type of sensitizer has many advantages.…”
Section: Sensitization Mechanismmentioning
confidence: 99%